From gene to therapy in spinal and bulbar muscular atrophy: Are we there yet?. (15th April 2018) - Pennuto, Maria; Rinaldi, Carlo
Abstract: Abnormal polyglutamine expansions in the androgen receptor (AR) cause a muscular condition, known as Kennedy's disease or spinal and bulbar muscular atrophy (SBMA). The disease is transmitted in an X-linked fashion and is clinically characterized by weakness, atrophy and fasciculations of the limb and bulbar muscles as a result of a toxic gain-of-function of the mutant protein. Notably, affected males also show signs of androgen insensitivity, such as gynaecomastia and reduced fertility. The characterization of the natural history of the disease, the increasing understanding of the mechanism of pathogenesis and the elucidation of the functions of normal and mutant AR have offered a momentum for developing a rational therapeutic strategy for this disease. In this special issue on androgens and AR functions, we will review the molecular, biochemical, and cellular mechanisms underlying the pathogenesis of SBMA. We will discuss recent advances on therapeutic approaches and opportunities for this yet incurable disease, ranging from androgen deprivation, to gene silencing, to an expanding repertoire of peripheral targets, including muscle. With the advancement of these strategies into the clinic, it can be reasonably anticipated that the landscape of treatment options for SBMA and other neuromuscular conditions will change rapidly in the near future. Highlights: Polyglutamine expansions in the androgen receptor cause spinal and bulbar muscular atrophy, also known as Kennedy's disease. Clinical features: genotype/phenotype correlation. From gene to protein: Molecular pathways to neurodegeneration. Development of novel therapeutic approaches.